Ejercicios físicos para mejorar la motricidad gruesa de los adultos mayores del hogar “Estancia de Paz” Francisco Valdivieso, del barrio Landangui de la parroquia Malacatos del cantón Loja, en el periodo marzo-julio 2015 - Jiménez Ganda, Olga Gabriela (2015)
The present thesis entitled: PHYSICAL EXERCISES TO IMPROVE GROSS MOTOR SKILLS OF ELDERLY PEOPLE AT “ESTANCIA DE PAZ” FRANCISCO VALDIVIESO NURSING HOME, LOCATED AT LANDANGUI NEIGHBORHOOD, MALACATOS PARISH OF LOJA CANTON, IN THE PERIOD MARCH-JULY 2015. The general objective of the present thesis was: To optimize the gross motor skills through physical exercises in elderly people at "Estancia de Paz" Francisco Valdivieso Nursing Home. This work is part of action research model, through the intervention, which has a mixed character approach, in other words quantitative-qualitative, for that research work was required the use of three types of study application, firstly the descriptive type, correlational and explanatory. The methods applied fall into three areas: theoretical-diagnostic, design and planning of the alternative, and evaluation and assessment of the alternative effectiveness, to carry out this research work the following methods were required: the Analytic-Synthetic method, deductive - inductive, historical - logical, descriptive, dialectic, Phenomenological, empirical methods and finally the statistical methods. Along the research development was taken account a population of 6 elderly, 5 of them presenting a gross motor skill affected, while one of them presented a very affected gross motor skill, making a total sample of six elderly people to work totally in the topic to be investigated. After the implementation of the physical exercises program it is important to mention that an improvement was evident in the gross motor skills of elderly people; although most of them came from a gross motor skills affected they got a normal gross motor skills, so the use of physical exercises program is really recommended to improve elderly people’ gross motor skills